Pengaruh Penambahan Ekstrak Buah Pepaya Muda Terhadap Tingkat Pertumbuhan dan Kelangsungan Hidup Ikan Mas (Cyprinus carpio) - Hamsir, Widianto; Juliana; Lamadi, Arafik (Transbahasa, 2024)
This research aims of determine the effect of adding papaya extract which countains the papain enzyme on the growth and survival of goldfish (Cyprinus carpio). It is conducted for 35 days at the Andalas Fish Seed Center (BBI), Kota Tengah, Gorontalo Province. The research method applies a completely randomized design (CRD) with 4 treatments and 3 replications. It is done by adding a dose of papaya extract containing the papain enzyme as P1 (Control), P2 (0,25g), P3 (0,50gr), P4 (0,75 gr). Moreover, the parameter observed include weight and length growth as well as survival. The result show that the addition of papaya extract to feed can increase the growth rate of the goldfish see weight with the best value of 0,48% in the P3 treatment and 0,65% in length growth. Meanwhile, the lowest value is shown in the P1 treatment of 0,25% for weight and 0,46% for length. Futhermore, the highest survival is achieved in the P4 treatment at 81,67% and the lowest in the P1 treatment at 33,33%. The addition of papaya extrac to the feed does not affect the growth in its length and weight but does affect the survival. On the other hand, the water quality during the research ranges from 27-27,2oC, with pH 8,0-8,1 and DO 5,8-6,2 Mg/L.